Mechanochromic LLDPE Films Doped with NIR Reflective Paliogen Black. Issue 1 (21st October 2020) - Micheletti, Cosimo; Minei, Pierpaolo; Carlotti, Marco; Mattoli, Virgilio; Muniz‐Miranda, Francesco; Perfetto, Anna; Ciofini, Ilaria; Adamo, Carlo; Ruggeri, Giacomo; Pucci, Andrea
Abstract: The perylene bisimide derivative Paliogen Black (P‐black) is proposed as a new chromogenic probe that shows visible (vis) and near‐infrared (NIR) responses after mechanical solicitations of host linear low‐density polyethylene (LLDPE) films. P‐black is reported to display strong absorption in the vis spectrum and unusual reflective and cooling features in the NIR region. Uniaxial deformation of the 2.5, 5, and 10 wt% P‐black/LLDPE films yields a dichroic absorption under polarized light with color variations attributed by the computational analysis to the distinct anisotropic behavior of the transition dipole moments of P‐black chromophores. When LLDPE films are deformed, P‐black aggregates reduce their size from ≈30–40 µm to ≈5–10 µm that, in turn, causes reflectivity losses of about 30–40% at the maximum elongation. This gives rise to warming of 5–6 °C of the locally oriented film placed in contact with a black substrate under the illumination with an IR lamp for 5 s. These features combined with the high sensitivity of the vis‐NIR response toward mechanical solicitations render P‐black as a new solution to detect uniaxial deformations of plastic films through both optical and thermal outputs. Abstract : Near‐infrared (NIR) reflective perylene bisimide derivative Paliogen Black (P‐black) endows linear low‐density polyethylene (LLDPE) films with opto/thermal responsiveness towards mechanical deformation. P‐black pigment aggregates experience exfoliation during the deformation process, thus causing a dichroic behavior in polarized light in the visible and a strong reduction of the reflectivity in the NIR that causes warming of the locally oriented film portion.